The use of Kodak photoflo-600 solution in cellulose acetate electrophoresis - O. S., Selvaraj; M., Sekaran; J. M., Pandaran; T. K., Mukherjee; Tan, S. G.; Barker, J. S. F. (1990)
The presence of KODAK Photoflo-600 (Cat.No.4055786),which contains ethylene glycol,in the cellulose acetate electrophoresis (CAE) buffers enhances the activities and sharpens the bands formed by several goat and buffalo blood enzymes on gels. This solution also overcame the problems encountered with overheating in some buffer systems. Its presence in the gel buffer also made it easier to soak the gel strips without any entrapment of air bubles. Malic enzyme (ME),malate dehydrogenase (MDH). 6-Phosphoglucose dehydrogenase(6pgdh). Glucose phosphate isomerase (GPI). Isocitrate dehydrogenase (IDH) and NADH-Diaphorase (NADH-DIA) from both buffaloes and goats exhibited ,arked improvement in band resolution and staining properties.